2015
DOI: 10.1021/acs.analchem.5b02701
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Specific Stable Carbon Isotope Analysis of Chlorofluorocarbons in Groundwater

Abstract: Chlorofluorocarbons (CFCs) and hydrochlorofluorocarbons (HCFCs), controlled substances due to their role in stratospheric ozone loss, also occur as dissolved contaminants in groundwaters. Stable carbon isotopic signatures may provide valuable new information on the fate of these compounds as has been seen for other priority hydrocarbon contaminants, but to date no method for extraction and isotopic analysis of dissolved CFCs from groundwaters has been developed. Here we describe a cryogenic purge and trap syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Stable carbon isotope effects associated with nonequilibrium volatile loss of the pure phase and compounds dissolved in water were determined. Previous studies (Table ) reported inverse VPIE for pure-phase evaporation of TCE (ε = +0.24 to +0.35 ‰), , CFC-11 (ε = +1.7 ± 0.1 ‰), and CFC-113 (ε = +1.1 ± 0.1 ‰) . In the current study, pure-phase evaporation of chloroform resulted in an enrichment factor of +1.2 ± 0.1‰.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Stable carbon isotope effects associated with nonequilibrium volatile loss of the pure phase and compounds dissolved in water were determined. Previous studies (Table ) reported inverse VPIE for pure-phase evaporation of TCE (ε = +0.24 to +0.35 ‰), , CFC-11 (ε = +1.7 ± 0.1 ‰), and CFC-113 (ε = +1.1 ± 0.1 ‰) . In the current study, pure-phase evaporation of chloroform resulted in an enrichment factor of +1.2 ± 0.1‰.…”
Section: Resultssupporting
confidence: 61%
“…Quantification of organics dissolved in water was carried out via headspace analysis by gas chromatography (GC) with flame ionization detection (FID). Details and specifics are published elsewhere . Overall precision of this method was better than 5% (1σ).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compound specific stable carbon isotope analysis was carried out by closely following a previously published protocol. 20 Briefly, for headspace analysis, gas samples were injected directly into the GC by using a gastight syringe. After separation on a GSQ column mounted in a Varian 3400, compounds were transformed to CO2 in the connected combustion furnace and transferred to the isotope ratio mass spectrometer (Finigan MAT 252).…”
Section: Methodsmentioning
confidence: 99%